Growth and Osteogenic Differentiation of CD117+ Dental Pulp and Periodontal Ligament Cells - Ferry Sandra; Janti Sudiono; Ciptadhi Tri Oka Binartha; Angliana Chouw; Melanie Sadono Djamil (The Prodia Education and Research Institute (PERI), 2017)
BACKGROUND: Dental pulp stem cell (DPSC) and periodontal ligament stem cell (PDLSC) have been suggested as valuable seed cells for bone engineering, suggesting that both stem cells are potential osteogenic sources. Since DPSC and PDLSC seem like to have similar potential in bone formation, we conducted a study to compare morphology, immunophenotype and cell growth of DPSC and PDLSC isolated from the same teeth.METHODS: Human dental pulps and periodontal ligaments were obtained from freshly extracted partial impacted third molar teeth. Collected samples were digested with type I collagenase. Resulted cell suspension was washed and cultured. For biomarker identification, the cells were fixed and bound with anti-fluorescein isothiocyanate (FITC)-cluster of differentiation (CD)117 antibody. For cell growth quantification, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was used. Meanwhile for osteogenic differentiation, the cells were cultured in osteogenic medium for 1-3 weeks, fixed and stained with alizarin red.RESULTS: Morphology of dental pulps cell (DPC) and periodontal ligament cell (PDLC) in passage 5 was similar. Clear CD117 green fluorescence of DPC and PDLC in passage 5 was observed. Cell growth rate of PDLC was higher than the one of DPC, 0.3858 and 0.3848 respectively. DPC formed bone nodule on the third week culture in osteogenic medium, while PDLC showed bone nodule formation on the second week culture.CONCLUSION: We suggest that DPC and PDLC are potential seed cells for osteogenic regeneration, since they had cell growth capacity and osteogenic differentiation, particularly PDLC that had faster osteogenic differentiation.KEYWORDS: dental pulp, periodontal ligament, cell, growth, osteogenic differentiation